Peran Dukungan Keluarga denganKetepatan Pemberian MP-ASI pada Bayi Usia 6–12 Bulan - Bella Maharani Putri; Nutrisia Nu’im Haiya; Iwan Ardian (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Providing complementary foods (MP-ASI) is an important stage in the growth and development of infants after 6 months of age. However, many mothers still provide MP-ASI too early, which can have a negative impact on the baby's health. This study aims to determine the relationship between family support and the provision of MP-ASI to infants aged 6–12 months in Wringinjajar Village, Demak Regency. This study is a quantitative study using a cross-sectional approach. The total sampling technique used was 80 respondents. Data collection used a questionnaire, which was then analyzed using the chi-square test. The results of this study showed that 70 (87,5%) respondents received good family support when providing complementary feeding, and 10 (12,5%). respondents received less family support when providing complementary feeding. The chi-square test results obtained a ρ value of 0.001. There is a significant relationship between family support and the provision of complementary feeding to babies aged 6-12 months.